(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article briefly describes the military battles, hard work, courage, intellectual victories of the great defender of the country, the lion of Turan Jaloliddin Manguberdi in the defense of the Motherland, his courage in defeating the enemy.